Situating and Interrogating Contemporary Australian Rural Education Research - Beverley Moriarty; Patrick Alan Danaher; Geoff Danaher (Journal of Research in Rural Education, 2003)
This opening article in this special issue about Australian rural education research develops three key points. First, the Australian literature reflects the complexities of defining the terms regional, rural, and remote, with many definitions deriving from a fixed and disabling urban-rural binary. That literature also contains a number of success stories of educational innovations in rural Australia. Second, the conceptual and methodological resources underpinning the Australian literature need to be interrogated to ensure that they avoid deficit constructions of rural Australia in favor of more productive understandings that recognize and value rural educational innovations. Third, the articles in this collection provide points of potential dialogue between American and Australia rural education researchers committed to mapping and celebrating diversity and innovation.